Analysis of Factors Influencing Angel Investor Funding Decisions in Startup Companies - M. Alifudin Sena; Sri Mulyati (Cita konsultindo, 2025)
This study aims to identify the factors that influence angel investors' decision to provide funding to start-up companies. The main issue raised is how founder characteristics, product attributes, financial management, and market research affect angel investors' investment funding decisions. This researcher uses quantitative methods with 120 respondents using purposive sampling. The data in this study were obtained by filling out a questionnaire by the respondents. There are 19 questions that must be answered by respondents via Google Form. PLS-SEM using SmartPLS was selected in the study to conduct data analysis. This study found that market research significantly affects angel investor funding decisions, Start-up Founders significantly affect angel investor funding decisions, Product significantly affects angel investor funding decisions, Product significantly affects angel investor funding decisions, and Financial Management significantly affects angel investor funding decisions.